Atom economical C-N bond formation catalyzed by N-heterocyclic carbene based ruthenium complexes - Chen, Cheng (2012)
Direct amide synthesis from alcohols and amines is a highly environmentally friendly process with high atom economy. It was reported that in situ generated NHC-based Ru catalytic systems, active for alcohol amidation with amines, did not show good activity in the amide formation of aldehydes with amines, forming imines as major products, even though aldehydes were proposed as intermediates formed by dehydrogenation of alcohols. Based on our previous catalytic system using a commercially available ruthenium complex [Ru(p-cymene)Cl2]2, an N-heterocyclic carbene ligand, a base and pyridine, we demonstrated an improved method for the direct amide synthesis from aldehydes and amines. Various amides were synthesized from aldehydes and amines in moderate to good yields using this method. For alcohol amidation reactions with amines, previous catalysts showed excellent activity for amidation reactions between alcohols and primary amines, but limited activity for those between alcohols and secondary amines. The direct amidation of alcohols with challenging secondary amines was achieved with a well-defined N-heterocyclic carbene based ruthenium complex. Involvement of ester intermediates was suggested unlike the previous amidation with less sterically hindered alcohols and amines. During investigation of the substrate scope for the direct amide synthesis from alcohols and amines, selective sp3 C-O bond cleavage with amide formation was observed in reactions of 3-alkoxy-1-propanol derivatives and amines. This is the first catalytic C-N bond formation via sp3 C-O cleavage. The cleavage only occurs at the C3-O position even with 3-benzyloxy-1-propanol. 3-alkoxy-1-propanol derivatives reacted smoothly with benzyl amine to give two amide products. Treatment of different amines with 3-benzyloxy-1-propanol also resulted in the selective C-O cleavage with C-N bond formation. Based on experimental results, O-bound and C-bound Ru enolate complexes were proposed as key intermediates in the reaction. Moreover, kinetic isotope experiments demonstrated two independent processes from the whole reaction and identified the respective rate-determining steps. Deuterium-labeling experiments showed that acrolein or Ru-bound acrolein species was another important intermediate.